2022
DOI: 10.1038/s41598-022-13041-3
|View full text |Cite
|
Sign up to set email alerts
|

The melanopsin-mediated pupil response is reduced in idiopathic hypersomnia with long sleep time

Abstract: Idiopathic hypersomnia (IH), characterized by an excessive day-time sleepiness, a prolonged total sleep time on 24 h and/or a reduced sleep latency, affects 1 in 2000 individuals from the general population. However, IH remains underdiagnosed and inaccurately treated despite colossal social, professional and personal impacts. The pathogenesis of IH is poorly known, but recent works have suggested possible alterations of phototransduction. In this context, to identify biomarkers of IH, we studied the Post-Illum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 66 publications
1
8
0
Order By: Relevance
“…More recently, we showed for the first time that patients with IH with prolonged sleep time had reduced PIPR as compared with healthy subjects (Rach et al, 2022), indicating a lower reactivity of the melanopsinergic system. We suggested that a reduced sensitivity of the melanopsin system could lead to a phenotype of both decreased overall alertness and delayed sleep-wake timing in IH with long sleep time (Rach et al, 2022). This reduced ipRGCs integration of the light signal could also be present in individuals suffering from another hypersomnia subtype, and contribute to a "light-related vulnerability to sleepiness", but this has never been explored.…”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…More recently, we showed for the first time that patients with IH with prolonged sleep time had reduced PIPR as compared with healthy subjects (Rach et al, 2022), indicating a lower reactivity of the melanopsinergic system. We suggested that a reduced sensitivity of the melanopsin system could lead to a phenotype of both decreased overall alertness and delayed sleep-wake timing in IH with long sleep time (Rach et al, 2022). This reduced ipRGCs integration of the light signal could also be present in individuals suffering from another hypersomnia subtype, and contribute to a "light-related vulnerability to sleepiness", but this has never been explored.…”
Section: Introductionmentioning
confidence: 78%
“…Women and men aged 18 years or older with a diagnosis of IH ( n = 36), NT1 ( n = 27) or healthy controls ( n = 43) were included between 2020 and 2022 at the Sleep Disorders Center of the University of Strasbourg. There is a major overlap of IH and control participants with our previous study, as several participants (28 IH patients and 29 healthy subjects) were also included in this work (Rach et al, 2022). Given the heterogeneity of IH phenotypes and in order to identify biomarkers of hypersomnia subtypes, only IH patients with prolonged sleep time were included in the study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations